Indirect Reduction Maneuver and Minimally Invasive Approach for Displaced Proximal Humerus Fractures in Elderly Patients - Jung, Sung-Weon (The Korean Orthopaedic Association, 2013)
BACKGROUND: This study examined the clinical outcomes of indirect reduction maneuver and minimally invasive approach for treating displaced proximal humerus fractures in patients older than 60. METHODS: Thirty-two patients (11 male and 21 female) who had undergone treatment for displaced proximal humerus fracture were evaluated. The mean age of the patients was 72.4 years (range, 60 to 92 years). All cases were followed up for at least 12 months. All patients were interviewed and evaluated on the visual analog scale, with gender-specific constant score correction for age, standardized X-rays to check the neck-shaft angle (NSA) and the presence of medial support, and bone mineral density. Statistical analysis was performed with a multiple regression analysis. RESULTS: The average visual analog scale score was 2.4, and the average gender-specific constant score correction for age was 80.6 points. Final functional outcomes were 8 excellent, 15 good, 7 fair, and 2 poor. The average NSA was 122.8°; and the radiological results were 20 good, 11 fair, and 1 poor. There was significant difference of the gender-specific constant score for age between the group of NSA more than 110° and the group of NSA less than 110° (p = 0.00). There were 26 cases with and 6 cases without medial support, with significant difference between the gender-specific constant score correction for age of these groups (p = 0.01). Complications occurred in 4 patients (12.5%). CONCLUSIONS: The indirect reduction maneuver and minimally invasive approach were safe and reliable options for the treatment of displaced proximal humerus fractures in the elderly patients. An inadequate reduction (i.e., less than 110° NSA) or lack of medial support (e.g., no cortical or screw support) were significant factors contributing to poor functional outcomes.